One Amazon: A Personal Environmental History. An Interview with Susanna Hecht - Dutra e Silva , Sandro; Lerner, Adrián; Pádua, José Augusto (Historia Ambiental Latinoamericana y Caribeña (HALAC) revista de la Solcha, 2023)
One Amazon: A Personal Environmental History. An Interview with Susanna Hecht